PENANGANAN SENGKETA PERDAGANGAN INTERNASIONAL MELALUI WTO (WORLD TRADE ORGANIZATION) - Imawan Dicky Prasudhi (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2007)
WTO (World Trade Organization) is negotiation forum to discuss the commerce problem that arising out among contracting parties - Section III : 3 Agreement of Establishing the Multilateral Trade Organization. WTO have also made an arrangement concerning of dispute settlement which arranged in Annex 2 " Understanding on Rules and Procedures Governing the Settlement of Disputes (DSU- Disputes Settlement Understanding )", that complete of dispute settlement in GATT 1947. Beside that was also formed a special body to handle dispute was called DSB ( Dispute Settlement Body). WTO also give some alternative of peaceful means of dispute settlement, for example by good offices, conciliation or mediation to the lawsuits even if that dispute have been raised to WTO.